Sustainable Entrepreneurship (SE): A Revised Model Based on Triple Bottom Line (TBL) - Abdul Majid, Izaidin; Koe, Wei Loon (2012)
Throughout the years, researchers have suggested several fields of entrepreneurship studies, such as regular entrepreneurship, green entrepreneurship, social entrepreneurship and sustainable entrepreneurship. This literature review focused on sustainable entrepreneurship, in which a definition was proposed. Then, based upon the concept of triple bottom line, a revised model of sustainable entrepreneurship was suggested at the end of paper. The model consisted of four domains, namely economical, social, ecological and cultural. Thus, in order to be acknowledged as true sustainable entrepreneurs, they are required to give equal priority to all of the four domains suggested in the model.